Numerical analysis of flexural and shear behaviors of geopolymer concrete beams - Mehmet Cemal Acar; Ahmet Şener; Ahmet Özbayrak; Ali İhsan Çelik (Journal of Sustainable Construction Materials and Technologies, 2022)
Geopolymer concrete (GPC) is obtained by activating industrial wastes such as fly ash with chemical liquids such as sodium hydroxide (NaOH) and sodium silicate (Na2 SiO3). In order to use environmentally friendly GPC obtained from industrial wastes instead of portland cement concrete (OPC), its behavior in structural elements is important and should be investigated in detail. Load-displacement characteristics, flexural and shear stiffnesses and crack development of samples were obtained by numerical analysis. The GPC beams to be an alternative to OPC beams, their mechanical properties and fracture modes must be at least as much as OPC. As a result of the analyses, it was determined that the 110x20x15 cm GPC beams with compression reinforcements of 2Φ8 and tension reinforcements of 2Φ8, 3Φ14 and 2Φ18, respectively, showed similar flexural, shear and crack development with OPC beams. Simulations of GPC beams were made up to the breaking point, contributing to the understanding of its behavior.